ECOLOGICAL, ECONOMICAL AND TECHNOLOGICAL ASPECTS OF DEVELOPMENT. DECOMPOSITION ANALYSIS OF ENERGY CONSUMPTION RELATED TO CO2 EMISSIONS IN ECUADOR (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Decomposition Analysis (DA) is widely applied in understanding changes of economical, technological, environmental, and different indicators as energy consumption, employment and other socio-economic indicators. This work discusses the DA methodology and is applied within Ecuadorian case. We present the used technique, the applied mathematical methodology and the construction of an appropriate identity to measure the change of CO2 emission in Ecuador during the period of 1980-2025. Change is measured in both macro and disaggregated sectorial level. Specific aspects related to the application of DA to both the historical period (1980-2010) and in medium term prevision (2011-2025) for four proposed macro scenarios are discussed. The findings show that the evolution of the BS scenario, which implies a trend-growth GDP scenario, is almost a flat curve, however the CO2 emission increases steadily because of the absence of attenuation measurements. A similar behavior, although slightly sloping down, is observed for SC-2 scenario, where a rapid growth of the GDP is assumed without any attenuation action regarding to CO2 emissions. The other two scenarios, SC-3 and SC-4 show a steady reduction of the Dtot = Dact ratio due to the changes in the sectorial structure and in the energy mix, which allows compensation of rapid GDP growth. This analysis suggests that, with the appropriate changes in the energy mix, the sectorial structure, and the share of renewable energies, Ecuador can move into a more environmentally sustainable state.